1994
DOI: 10.1002/hep.1840200508
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C in Hiv–Infected Patients With and Without Aids: Prevalence and Relationship to Patient Survival

Abstract: Background: Limited information is available about the prevalence of hepatitis C virus in patients with human immunodeficiency virus in relation to specific risk factors or about the influence of hepatitis C virus coinfection on survival. This retrospective study addressed these questions. Methods: The study population consisted of 512 predominantly non-intravenous drug-using male homosexuals, 224 of whom had AIDS. Samples positive for hepatitis C virus antibody by second-generation enzyme immunoassay were fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
49
2
4

Year Published

1996
1996
2007
2007

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(55 citation statements)
references
References 17 publications
0
49
2
4
Order By: Relevance
“…Some studies prior to the advent of highly active anti-retroviral therapy (HAART) suggested that survival and progression to AIDS were the same in patients with HCV/ HIV co-infection as in those with HIV alone [14][15][16], while others suggested an adverse effect [11][12][13][14][15][16][17]. In the pre-HAART era, HCV infection was deemed an irrelevance as it was HIV that affected morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies prior to the advent of highly active anti-retroviral therapy (HAART) suggested that survival and progression to AIDS were the same in patients with HCV/ HIV co-infection as in those with HIV alone [14][15][16], while others suggested an adverse effect [11][12][13][14][15][16][17]. In the pre-HAART era, HCV infection was deemed an irrelevance as it was HIV that affected morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Patients co-infected with both HIV and HCV have a higher risk of progression to chronic liver disease than those infected with HCV alone 15,17,19 . However, little is known about the effect of co-infection on the progression of HIV disease 4,14,21 .…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16] There are conflicting reports concerning whether HCV infection alters the course of HIV. 17 Some studies before the advent of highly active anti-retroviral therapy (HAART) suggested that survival and progression to AIDS were the same in patients with HCV/HIV co-infection as in those with HIV alone 18,19 whereas others suggested an adverse effect. 13,20 In the pre-HAART era, HCV infection was deemed an irrelevance as it was HIV that affected morbidity and mortality.…”
mentioning
confidence: 99%